Molecular basis for pericyte-induced capillary tube network assembly and maturation - Kemp, Scott S.; Lin, Prisca K.; Sun, Zheying; Castaño, Maria A.; Yrigoin, Ksenia; Penn, Marlena R.; Davis, George E. (Frontiers in Cell and Developmental Biology, 2022)
Here we address the functional importance and role of pericytes in capillary tube network assembly, an essential process that is required for vascularized tissue development, maintenance, and health. Healthy capillaries may be directly capable of suppressing human disease. Considerable advances have occurred in our understanding of the molecular and signaling requirements controlling EC lumen and tube formation in 3D extracellular matrices. A combination of SCF, IL-3, SDF-1α, FGF-2 and insulin (“Factors”) in conjunction with integrin- and MT1-MMP-induced signaling are required for EC sprouting behavior and tube formation under serum-free defined conditions. Pericyte recruitment to the abluminal EC tube surface results in elongated and narrow tube diameters and deposition of the vascular basement membrane. In contrast, EC tubes in the absence of pericytes continue to widen and shorten over time and fail to deposit basement membranes. Pericyte invasion, recruitment and proliferation in 3D matrices requires the presence of ECs. A detailed analysis identified that EC-derived PDGF-BB, PDGF-DD, ET-1, HB-EGF, and TGFβ1 are necessary for pericyte recruitment, proliferation, and basement membrane deposition. Blockade of these individual factors causes significant pericyte inhibition, but combined blockade profoundly interferes with these events, resulting in markedly widened EC tubes without basement membranes, like when pericytes are absent.